2021
DOI: 10.16993/bbl
|View full text |Cite
|
Sign up to set email alerts
|

Narrowed Lives: Meaning, Moral Value, and Profound Intellectual Disability

Abstract: What is day-to-day life like for people with profound intellectual and multiple disabilities who live in group homes? How do they express their desires and wishes? How do care workers think about them and treat them? Do they have basic rights to activities most of us take for granted: activities like sociability, sexuality, and moral affirmation? Narrowed Lives is an illuminating portrait of what life is like in Finnish group homes where adults who have profound intellectual and multiple disabilities live the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 124 publications
(173 reference statements)
1
26
0
1
Order By: Relevance
“…Importantly, the assessment is usually made by a social worker only minimally acquainted with the person. Such limited acquaintance may pose as a barrier as studies, including those focused on people with profound and multiple disabilities, have shown that when choices are communicated to them in meaningful ways by people familiar to them, they often have unexpected abilities to make decisions (Vehmas & Mietola, 2021 ). Moreover, studies show that having close relationship and personal knowledge about the person is often necessary to reveal and give meaning to nonverbal forms of communication (Watson et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the assessment is usually made by a social worker only minimally acquainted with the person. Such limited acquaintance may pose as a barrier as studies, including those focused on people with profound and multiple disabilities, have shown that when choices are communicated to them in meaningful ways by people familiar to them, they often have unexpected abilities to make decisions (Vehmas & Mietola, 2021 ). Moreover, studies show that having close relationship and personal knowledge about the person is often necessary to reveal and give meaning to nonverbal forms of communication (Watson et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, research involving persons with PIMD has emphasized deficits, mostly through the voice of proxies (Nind & Strnadova, 2020). This study aims to ground arguments on lived experiences, valuing the lives of persons with PIMD (Vehmas & Mietola, 2021). Thus, it calls for methods that can include such perspectives, and a qualitative approach (Bryman, 2016) was applied.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has identified a paucity of knowledge about how to practically go about ensuring the support to enable self-determination (Nicholson et al, 2021). While professionals might endorse the principle of self-determination, knowledge about how to support it is lacking (Vehmas & Mietola, 2021). A model such as the circle of support (Watson, 2012) provides fruitful structures for the related concept of supported decision-making (Watson et al, 2019), but filling the void regarding details in the relationship between the professional and the person with PIMD can inform best practices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very often it is not wrong at all,” basing his views on the relative capacities of nonhuman animals (Singer, 1979, p. 191). His position has been forcefully challenged (Carlson, 2010; Kittay & Carlson, 2010; Vehmas & Mietola, 2021) but he persists.…”
Section: Useful Contradictionsmentioning
confidence: 99%